Attitude Towards Environmental Education of Primary Graduates in Bangladesh (Teacher’s World: Journal of Education and Research, 2024)
The study focused on primary graduates’ attitude towards Environmental Education (EE) in Bangladesh. The study was based on attitude survey in the light of national and international research done on EE and education for sustainable development and the different related policies here in Bangladesh. The study is quantitative in nature, adopting quantitative data. The data was collected from 16 main stream government secondary schools in four different regions in Bangladesh. A total of 480 primary graduates were constituted as sample for the study. The data was collected through a Likert scale. While the development of tools emphasis was given to the curriculum of primary education and terminal competencies related to EE at primary level in Bangladesh. To assess the students’ attitude towards EE a composite score was developed by accumulating total score and classified into four groups as Highly favorable, Favorable, Moderately favorable and Less favorable using respective range boundary. The study reveals that a total of 54.60 percent students showed a favorable attitude towards EE. On the other hand, a total of 9.20 percent, 24.20 percent and 12.10 percent students showed a highly favorable, moderately favorable, and less favorable attitude towards EE respectively. The study also showed that there were a variation within and in- between regions and gender resulted in respect of attitude towards EE. On the basis of the findings of the study, it was concluded that the respondents expressed variations in their perceptions to EE, and showed different attitudes towards environment. This study recommended several initiatives for up-grading the students’ attitude level towards EE based on the findings. The major initiatives that need to be taken are- highly favorable attitude towards EE should be developed among the students in Bangladesh; EE should be introduced largely in primary education through introducing child-friendly contents; teachers’ pedagogical knowledge and skills should be enhanced on EE; awareness of parents, teachers and education officials on EE should be developed; environmental education should be started at the very early age of the learners at school as well as at home. More importantly, this study recommended developing children’s values to practice their learning of EE in real life context.Teacher’s World: Journal of Education and Research, 49 (1), 33-47